Treatment of textile wastewater using monolayered ultrafiltation ceramic membrane fabricated from natural kaolin clay. Issue 21 (19th September 2021) - Bousbih, Saida; Errais, Emna; Darragi, Fadila; Duplay, Joelle; Trabelsi-Ayadi, Malika; Daramola, Michael Olawale; Ben Amar, Raja
ABSTRACT: Fabrication, characterization and application of ceramic membrane developed from Tunisian natural kaolin clay for textile wastewater treatment are presented in this study. The morphology and properties of the resulting membrane sintered at 1000°C for 3 h were then determined by Scanning Electron Microscopy (SEM), mechanical and chemical resistance and water permeability. Separation performance of the membrane was evaluated during the treatment of textile wastewater. SEM images reveal the homogeneous surface of the membrane. The membrane displayed good chemical and mechanical resistances as well. Its permeability was of 21.2 L.h −1 .m −2 .bar −1, indicating that separation performance could occur in the domain of Ultrafiltration (UF). Performances of the membrane during the treatment of raw and biologically pretreated textile effluents are promising in terms of the removal of colour (99% for the raw effluent and 100% for the biologically pretreated effluent), chemical oxygen demand (COD) (80% for the raw effluent and 93% for the biologically pretreated effluent) and turbidity (98% for the raw effluent and 100% for the biologically pretreated effluent). GRAPHICAL ABSTRACT: UF0001